2018
DOI: 10.1080/00071668.2018.1478064
|View full text |Cite
|
Sign up to set email alerts
|

Zataria multiflora essential oil reduces replication rate of avian influenza virus (H9N2 subtype) in challenged broiler chicks

Abstract: 1. The effect of Zataria multiflora essential oil on replication rate of the H9N2 virus in target organs was determined by real-time PCR. One-day-old broiler chicks were randomly divided into six groups and were challenged with H9N2 influenza. Two groups received either 20 or 40 µl/kg body weight/day Zataria multiflora essential oils (ZM) seven days before the challenge while two other groups received the essential oil at the same dosage but after H9N2 challenge. One group received 4 mg/kg body weight/day of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Several studies have reported the use of medicinal herbs in various forms including solvent extracts [44, 49, 50], essential oils [51], and powders [52]. Ghoke et al [49] reported that hydro-methanol leaf plant extracts decreased HA titers and virus genome copy numbers.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported the use of medicinal herbs in various forms including solvent extracts [44, 49, 50], essential oils [51], and powders [52]. Ghoke et al [49] reported that hydro-methanol leaf plant extracts decreased HA titers and virus genome copy numbers.…”
Section: Discussionmentioning
confidence: 99%
“…Based on a literature survey, we tested eighteen phytochemical compounds with reported antiviral properties including, Allicin (Xie et al,2020), Bornyl acetate , Capsaicin (Tang et al, 2020), Carvacrol (Bansal et al, 2020), Catechol (Mishra et al, 2020), Cinnamic acid (Silva et al, 2020), Curcumin (Bonfim et al, 2020), Eucalyptol (Patra et al, 2020), Gallic acid (Arsianti et al, 2020), Geraniol (Wei et al, 2020), Linalool (Del Bosco et al, 2020, Nicotinic acid (Corona et al, 2020), Phytic acid (Narayanaswamy and Esa 2018), Piperine (Chandani et al, 2019), Quercetin (Nile et al, 2020;Lopes et al, 2020;Aggarwa et al, 2020), Resorcinol (Lee et al, 2019), Terpinen-4-ol (Patra et al, 2020) and Viridiflorene (Shayeganmehr et al, 2018). Additionally, we have used as molecular docking controls, two FDA-approved old antimalarial drug, Chloroquine and Hydroxychloroquine (an analogue of chloroquine) recommended for treating COVID-19 patients (Gautret et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Groups that received oils before or after H9N2 challenge and amantadine-treated group showed reduced viral replication in the airways and gastrointestinal tract as compared to the control. The results showed that oil supplementation had a positive effect on reducing viral replication both in the gut and trachea of broiler chickens infected with H9N2 influenza, resulting in milder clinical symptoms and better results [Shayeganmehr et al 2018].…”
Section: Treatmentmentioning
confidence: 98%